Generating porosity during olivine carbonation via dissolution channels and expansion cracks - T. Xing; W. Zhu; F. Fusseis; H. Lisabeth; H. Lisabeth (Solid Earth, 2018)
The olivine carbonation reaction, in which carbon dioxide is chemically incorporated to form carbonate, is central to the emerging carbon sequestration method using ultramafic rocks. The rate of this retrograde metamorphic reaction is controlled, in part, by the available reactive surface area: as the solid volume increases during carbonation, the feasibility of this method ultimately depends on the maintenance of porosity and the creation of new reactive surfaces. We conducted in situ dynamic X-ray microtomography and nanotomography experiments to image and quantify the porosity generation during olivine carbonation. We designed a sample setup that included a thick-walled cup (made of porous olivine aggregates with a mean grain size of either  ∼  5 or  ∼  80 µm) filled with loose olivine sands with grain sizes of 100–500 µm. The whole sample assembly was reacted with a NaHCO3 aqueous solution at 200 °C, under a constant confining pressure of 13 MPa and a pore pressure of 10 MPa. Using synchrotron-based X-ray microtomography, the three-dimensional (3-D) pore structure evolution of the carbonating olivine cup was documented until the olivine aggregates became disintegrated. The dynamic microtomography data show a volume reduction in olivine at the beginning of the reaction, indicating a vigorous dissolution process consistent with the disequilibrium reaction kinetics. In the olivine cup with a grain size of ∼  80 µm (coarse-grained cup), dissolution planes developed within 30 h, before any precipitation was observed. In the experiment with the olivine cup of  ∼  5 µm mean grain size (fine-grained cup), idiomorphic magnesite crystals were observed on the surface of the olivine sands. The magnesite shows a near-constant growth throughout the experiment, suggesting that the reaction is self-sustained. Large fractures were generated as the reaction proceeded and eventually disintegrated the aggregate after 140 h. Detailed analysis show that these are expansion cracks caused by the volume mismatch in the cup walls, between the expanding interior and the near-surface which keeps a nearly constant volume. Nanotomography images of the reacted olivine cup reveal pervasive etch pits and wormholes in the olivine grains. We interpret this perforation of the solids to provide continuous fluid access, which is likely key to the complete carbonation observed in nature. Reactions proceeding through the formation of nano- to micron-scale dissolution channels provide a viable microscale mechanism in carbon sequestration practices. For the natural peridotite carbonation, a coupled mechanism of dissolution and reaction-induced fracturing should account for the observed self-sustainability of the reaction.